Microbial community structure and functional potential in a long-term uranium–nickel contaminated ecosystem - Chukwujindu, Christian; Kolton, Max; Fasakin, Olasunkanmi; Pathak, Ashish; Seaman, John; Chauhan, Ashvini (Frontiers in Microbiology, 2026)
This study examined the microbial community structure, functional potential, and resistance determinants in uranium (U)- and nickel (Ni)-contaminated soils from the Savannah River Site (SRS), a former nuclear materials production and waste collection facility operated by the U. S. Department of Energy (DOE). Soil cores were collected from the Steed Pond area, where long-term discharge of acidic wastewater resulted in spatially variable contamination levels. Concentrations of U and Ni in the collected samples ranged from 0.22–10.44 g kg−1 and 0.79–2.28 g kg−1, respectively. Shotgun metagenomic and high-throughput quantitative PCR (HT-qPCR) analyses revealed bacterial communities dominated by Pseudomonadota, Actinomycetota, and Acidobacteriota, with enrichment of taxa affiliated with genera known to include diazotrophic members (e.g., Bradyrhizobium and Burkholderia), alongside increased abundance of nitrogen fixation–related functional genes. Carbon and nitrogen cycle genes were generally well represented across samples, with selective shifts observed in acetate assimilation genes (acsA/acsE) and comparatively low abundance of hydrazine oxidoreductase (hzo), indicating pathway-specific variation rather than broad metabolic suppression. A total of 117 resistance-associated genes were identified, comprising 93 antibiotic-resistance genes (ARGs), 3 metal-resistance genes (MRGs), and 21 mobile genetic elements (MGEs). Strong positive correlations among ARGs, MRGs, and MGEs indicate co-selection and horizontal gene transfer, forming a genetically mobile resistome. Collectively, these findings demonstrate that long-term U–Ni contamination selects for metabolically versatile, diazotroph-enriched, and genetically mobile microbiomes. Such communities exhibit both resistance proliferation and bioremediation potential, providing key insights into microbial adaptation and ecosystem recovery in legacy nuclear-contaminated soils.